Sensibilité à la vitesse de déformation des matériaux composites unidirectionnels: Applications au verre E/époxy à 60 % de fibres - Rozycki, Patrick; Coutellier, Daniel (European Journal of Computational Mechanics, 2002)
Some experimental tensile and compressive tests, which have been performed for laminates of specific orientations, have displayed a strong dependence with regard to the strain rate as well for the material characteristics as for the behaviour type. Thus this paper proposes the theoretical integration of this strain rate sensitivity within an elastic plastic damaging law. The approach used is based on the definition of viscous fluids. All the theoretical developments are then implemented in a shell finite element within an explicit calculation code. The numerical simulations of experimental tensile and compressive tests show the validity and the reliability of the presented approach. Other tests, which concern linear and punctual impacts of composite plates, allow to lead to similar conclusions and to foresee the future prospects of this work.